MAGEH1 interacts with GADD45G and induces renal tubular cell apoptosis. - Gyu-Tae Shin (Public Library of Science (PLoS), 2021)
Background Melanoma-associated antigen H1 (MAGEH1) is a protein that belongs to melanoma-associated antigen (MAGE) superfamily. Growth arrest and DNA damage 45G (GADD45G) is a member of the DNA damage-inducible gene family which responds to environmental stresses. We have previously shown that GADD45G is a protein that promotes apoptosis of renal tubular cells in response to a nephrotoxic injury. In this study, we show evidence that MAGEH1 interacts with GADD45G and is involved in the induction of nephrotoxin-induced apoptosis of renal tubular cells. Methods Primary human renal tubular epithelial (HRE) cells and human kidney 2 (HK-2) cells were used in this study. To produce stable cell lines in which MAGEH1 expression was silenced, HRE cells were transduced with a lentiviral vector encoding a single guide RNA construct targeting the MAGEH1 gene. To knockdown GADD45G expression in HRE cells, a vector containing short hairpin RNA (shRNA) was used. We used short interfering RNAs (siRNA) to achieve transient silencing of genes in HK-2 cells. Recombinant adenoviruses were synthesized to overexpress MAGEH1 and GADD45G proteins. Human protein microarray was used to identify proteins that binds to GADD45G. Co-immunoprecipitation assays were then performed to confirm microarray results. Cell death was induced by cyclosporine A (CsA). Real-time quantitative PCR assay was used to evaluate gene expression levels. The degree of apoptosis and necrosis of cultured cells was evaluated by flow cytometry. Expression levels of caspases were examined using western blot analysis. Results We found that GADD45G bound to one protein spotted in the protein microarray, which was subsequently identified as MAGEH1. We confirmed the interaction between GADD45G and MAGEH1 protein using the co-immunoprecipitation assay. MAGEH1 gene expression was not altered by CsA-induced cytotoxic injury, whereas GADD45G gene expression was increased significantly upon CsA treatment. MAGEH1 expression was significantly downregulated in GADD45G knockdown HRE stable cells suggesting that MAGEH1 expression may be dependent on GADD45G expression. CsA-induced apoptosis was significantly reduced in MAGEH1 knockdown HRE stable cells which led to an increased survival of these cells. Similar results were observed in GADD45G knockdown HRE stable cells. Accordingly, CsA-induced apoptosis was significantly decreased in MAGEH1 siRNA and GADD45G siRNA transfected HK-2 cells. CsA-induced activation of caspase-7 and caspase-9 was inhibited in MAGEH1 knockdown HRE stable cells, and similarly in GADD45G knockdown HRE stable cells. Conclusions To the best of our knowledge, this is the first study to show that MAGEH1 interacts with GADD45G and that MAGEH1 is involved in caspase-dependent apoptosis of renal tubular cells induced by nephrotoxic drugs.